2016
DOI: 10.1155/2016/6836402
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation and Hemoglobin Levels in Hypertensive Patients: A Randomized Controlled Trial

Abstract: Epidemiological evidence suggests that circulating 25-hydroxyvitamin D (25OHD) levels are inversely associated with hemoglobin (Hb) levels and anemia risk. We evaluated whether vitamin D supplementation improves Hb levels and reduces anemia risk in hypertensive patients. Two hundred patients with 25OHD levels <75 nmol/L who attended the Styrian Vitamin D Hypertension Trial were included, of whom 188 completed the trial. Patients randomly received 2800 IU vitamin D3 daily or a matching placebo for eight weeks. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 41 publications
(40 reference statements)
2
19
0
Order By: Relevance
“…This is consistent with several studies in chronic kidney disease, cardiovascular disease, and the general population, which have described a positive association between vitamin D status and hemoglobin and/or an inverse association between vitamin D status and anemia (913, 15, 39, 40). Data from clinical trials have been mixed (3942), but recent studies in CKD and critically ill adult patient populations found that treatment with vitamin D or its analogues resulted in significant increases in hemoglobin concentrations (24, 43). This association has not been previously studied in IBD animal models or clinical studies.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with several studies in chronic kidney disease, cardiovascular disease, and the general population, which have described a positive association between vitamin D status and hemoglobin and/or an inverse association between vitamin D status and anemia (913, 15, 39, 40). Data from clinical trials have been mixed (3942), but recent studies in CKD and critically ill adult patient populations found that treatment with vitamin D or its analogues resulted in significant increases in hemoglobin concentrations (24, 43). This association has not been previously studied in IBD animal models or clinical studies.…”
Section: Discussionsupporting
confidence: 93%
“…However, very few trials have directly evaluated the effect of vitamin D treatment on hemoglobin concentrations or anemia. Among those that have, the results have been mixed, likely due to the differences in dosage and form of vitamin D administered, and the population studied [26-28]. In studies of patients with CKD, vitamin D or its analogues have been shown to increase hemoglobin concentrations [27, 29-31].…”
Section: Discussionmentioning
confidence: 99%
“…However, so far, the results of observational studies have not been confirmed by RCT (27)(28)(29). In a recent randomized control trial, Ernst et al (27) found no effect of daily vitamin D supplementation (2,800 IU) for 8 wk on hemoglobin level or the reduction of risk of anemia in non-anemic hypertensive patients with various vitamin D statuses. In addition, 12-wk vitamin D supplementation (600,000 IU once) did not improve the outcomes of parenteral iron therapy in subjects with both vitamin D deficiency and iron deficiency anemia (29).…”
mentioning
confidence: 98%
“…Several possible mechanisms for the association between vitamin D and anemia have been proposed, such as a direct stimulatory proliferative effect of vitamin D on bone marrow cells via VDR (24), silencing of inflammatory reactions that lead to anemia or chronic diseases (25) or parathyroid hormone (PTH)-dependent alteration in erythrocyte osmotic resistance (26). However, so far, the results of observational studies have not been confirmed by RCT (27)(28)(29). In a recent randomized control trial, Ernst et al (27) found no effect of daily vitamin D supplementation (2,800 IU) for 8 wk on hemoglobin level or the reduction of risk of anemia in non-anemic hypertensive patients with various vitamin D statuses.…”
mentioning
confidence: 99%